Окремі питання правового регулювання міграційної політики Європейського Союзу - Селюков, В. С.; Вуйма, А. Г.; ORCID: http://orcid.org/0000-0002-6690-6484; Seliukov, V. S.; Vuima, A.H. (Вісник Харківського національного університету внутрішніх справ. - 2016. - № 2 (73). - С. 126-135, 2016)
Розглянуто основні нормативно-правові акти ЄС з питань регламентації міграційних процесів. Визначено основні напрямки еволюції міграційної політики ЄС та сформульовано основні принципи, на яких має ґрунтуватися міграційна політика України в умовах євроінтеграції.

Some issues of combating migration processes that are underway in the European Union have been considered. The author has stressed on the necessity of strengthening police counteraction to illegal migration. Nowadays the problem of illegal migration is one of the main for the countries – members of the European Union. Greece could be a striking example of the operation of illegal migration process. From the information received by Greek secret services it is clear that groups of migrants are formed in Constantinople, Beirut, Side, Latakia, Addis Ababa, Asmara and Tripoli. Of course, these are small groups (5–20 people), accompanied by a guide, who get to their destination by air transport (bus, train or sea) and then walk, mostly at night time, crossing the border. Illegal (unlawful) migration is illegal movement across the state border, i.e. outside border crossing points or concealment from border and customs controls, using forged documents, visa or without them, independently or through the third parties, and living in the country without proper approval of the competent state authorities. Experts believe that illegal migration has become a highly profitable business of international criminal groups. Unmanaged growth of illegal migration promotes social phenomena such as crime, unemployment, the spread of dangerous diseases, the growth of illegal labor market, human trafficking, etc. It should be noted that considering the matters of illegal migration we must proceed from its understanding as a transnational phenomenon that operates outside the legal framework of the current legislation and takes the form of transnational organized crime.

Рассматрены основные нормативно-правовые акты ЕС по вопросам регламентации миграционных процессов. Определены основные направления эволюции миграционной политики ЕС и сформулированы основные принципы, на которых должна основываться миграционная политика Украины в условиях евроинтеграции.
Some issues of legal regulation of migration policy of the European Union
Отдельные вопросы правового регулирования миграционной политики Европейского Союзу
Селюков, В. С. Окремі питання правового регулювання міграційної політики Європейського Союзу / В. С. Селюков, А. Г. Вуйма // Вісник Харківського національного університету внутрішніх справ. - 2016. - № 2. - С. 126-135.
Селюков В. С., Вуйма А. Г. "Окремі питання правового регулювання міграційної політики Європейського Союзу." Вісник Харківського національного університету внутрішніх справ 2 (2016): 126-135.
Seliukov, V.S. and Vuima, A.H. (2016), “Some issues of legal regulation of migration policy of the European Union” [Okremi pytannia pravovoho rehuliuvannia mihratsiinoi polityky Yevropeiskoho Soiuzu], Visnyk Kharkivskoho Natsionalnoho Universytetu Vnutrishnikh Sprav, No. 2, pp. 126-135.
Keywords: Міжнародне право .International Law. Международное право; Наукові публікації. Scientific publications. Научные публикации; глобалізація; міграція; іммігранти; міграційна політика; Європейський Союз; євроінтеграція; globalization; migration; immigrants; migration policy; European Union; European integration; глобализация; миграция; иммигранты; миграционная политика; Европейский Союз; евроинтеграция